Designing Project-Based Narrative Text Using Quizzez - Ade Juanda; Syafrizal, Syafrizal; Pahamzah, John (Pencerah, 2024)
The pedagogy of today is not the same as it was in earlier decades. In the past, people used textbooks and blackboards in the classroom for educational purposes. People are using digital technology for learning these days. The goal of this project is to integrate Quizzez into a project-based learning approach for narrative texts. The Research and Development (R&D) approach is used in this investigation. Data collection through surveys and interviews is the first step. The findings demonstrated that students had high standards for the application of ICT in English language training. More particular, 42.4% of students expressed a desire to use digital learning resources more frequently when they are studying. Consequently, the author hopes to provide educational resources and evaluations that are easily incorporated with information and communication technology (ICT). Throughout the output production process, the author and instructor will collaborate to produce a more meaningful and successful outcome. The partner school will implement the outcome during the second week of January 2023.